Prevencia hematómu a edému po operáciach obsahu skróta - Dzurný, O; Sobek, M (Rozhledy v chirurgii, 1993)
Postoperative hematoma and edema are the most frequent complications of scrotal surgery. The authors refer their own experience with a simple, reliable method for prevention of postoperative hematoma and edema described by Oesterling.
Keywords: skrotum; Edema; Scrotum; mužské pohlaví; Methods; Humans; hematom; Hematoma; Postoperative Complications; edém; pooperační komplikace; lidé; Male; metody